Final Project Registration Management System (SIMANTA) [Case Study : University of Muhammadiyah Sidoarjo] - Danu Pamungkas; Mochamad Alfan Rosid (Procedia of Engineering and Life Science, 2022)
Muhammadiyah University of Sidoarjo is one of the private universities that provides final assignments and theses as one of the graduation requirements for obtaining Diploma and Bachelor degrees. The Final Assignment Registration Management System (SIMANTA) makes it easy for lecturers, students and admins to manage thesis data and provide information about the stages of the final project and thesis procedure for students. The development of this system was carried out to evaluate the existing system, namely SIMS UMSIDA. The previous system was still less than optimal in the procedures carried out in the implementation of the thesis because it was only used for the informatics study program. Therefore, with SIMANTA it can be used for all study programs and can distinguish data from each study program. The system design method in this study uses the prototype method and the data collection stage uses observation and interview techniques. The technology used for the SIMANTA design uses the Codeigniter version 4 framework, the PHP programming language version 7.4 and Bootstrap version 4x. So that the results of this study, the final assignment registration management system (SIMANTA) aims to provide convenience, manage data and provide information about thesis for lecturers, admins, and students at Muhammadiyah University of Sidoarjo.